Weaving the tastes of tradition: Uncovering the threads of India’s culinary identity amid globalisation - Ha van Trung; Du Quoc Dao (Research in Hospitality Management)
In the face of globalisation’s homogenising wave, this study serves as a beacon, illuminating the intricate web of factors that safeguard culinary heritage in India. The study hypothesised that a myriad of elements interweaves to form the fabric of food traditions, which in turn fortify collective identity. To validate this, the study engaged 696 individuals via an online survey, employing advanced statistical tools such as path analysis and partial least squares structural equation modelling (PLS-SEM) to unearth the core determinants of gastronomic lineage. Moreover, multiple regression analysis was utilised to measure the impact of these culinary practices on personal and cultural identity. The study’s revelations are profound, demonstrating that each of the 18 determinants meticulously chosen for this research significantly contributes to the crafting of Indian food heritage, thereby seasoning the identity of the future with the flavours of the past.